1998
DOI: 10.1046/j.1365-2672.1998.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

The isolation and prevalence of campylobacters from dairy cattle using a variety of methods

Abstract: Faecal samples from 94 dairy cows and 42 calves in three different herds were examined by a variety of techniques for campylobacters. Cefoperazone amphotericin teicoplanin (CAT) agar, modified cefoperazone charcoal deoxycholate agar (mCCDA), Karmali agar, and membrane filtration onto blood agar, were used with and without enrichment in CAT broth. Seventy-nine percent of cattle in herd A carried campylobacters, compared with 40% and 37.5% of cattle in herds B and C, respectively. Most animals carried only one s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(61 citation statements)
references
References 31 publications
1
58
2
Order By: Relevance
“…Since lpxA encodes UDP-GlcNAc acyltransferase, an enzyme required for lipid A biosynthesis (56), partial mutation of the lpxA gene in the primer annealing region is considered more likely than deletion of the gene. Given the composition of isolation media and the isolation conditions used, isolation of C. hyointestinalis is plausible and has been observed by other investigators (2,8,21,31). Although the isolation of thermotolerant C. fetus was fortuitous, other investigators have reported the isolation of similar atypical C. fetus strains from human and raw milk (13,32,62).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Since lpxA encodes UDP-GlcNAc acyltransferase, an enzyme required for lipid A biosynthesis (56), partial mutation of the lpxA gene in the primer annealing region is considered more likely than deletion of the gene. Given the composition of isolation media and the isolation conditions used, isolation of C. hyointestinalis is plausible and has been observed by other investigators (2,8,21,31). Although the isolation of thermotolerant C. fetus was fortuitous, other investigators have reported the isolation of similar atypical C. fetus strains from human and raw milk (13,32,62).…”
Section: Discussionmentioning
confidence: 96%
“…The media and isolation conditions used in this study were primarily developed for isolating C. jejuni and C. coli, and this may have biased detection in favor of these two species (2,5,11,15). Nevertheless, the prevalence of thermophilic campylobacters (C. jejuni, 34%; C. coli, 8%; other, 2%) in this study is generally concordant with the previous studies in which the prevalence of campylobacters in cattle ranged from 0.8 to 46.7%, depending on the isolation methods, herd size and type, geography, season, animal age, and number of animals investigated (9,21,28,41,47,61).…”
Section: Discussionmentioning
confidence: 99%
“…Others have previously isolated these two campylobacters from cattle at various frequencies (e.g., see references 3, 6, 16, 19, and 55). All media used to isolate Campylobacter species select for specific taxa and even genotypes (3,5,13,28,47). As a result, microbiological methods that employ selective media do not necessarily provide a true measure of the frequency and diversity of Campylobacter species associated with livestock and their feces.…”
Section: Discussionmentioning
confidence: 99%
“…The digestive tract of clinically normal cattle has been demonstrated to be a significant reservoir for a number of Campylobacter spp. [12], with prevalences of the enteropathogen in cattle ranging from 0-80%. Prevalences of Campylobacter in sheep have been shown to be generally lower with approximately 20% of animals intestinal carriers [197].…”
Section: Campylobacters and Other Food Animalsmentioning
confidence: 99%